2011
DOI: 10.1111/j.1447-0349.2010.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of group cohesiveness in therapeutic horticulture for clinical depression

Abstract: This study aimed to assess changes in psychological distress and social participation in adults diagnosed with clinical depression during and after participating in a therapeutic horticulture programme, and to investigate if the changes covaried with levels of group cohesiveness during the intervention. An intervention with a single-group design was repeated with different samples in successive years (pooled n = 46). In each year, five groups of 3-7 participants went through the intervention. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 53 publications
4
67
0
1
Order By: Relevance
“…In the study by Gonzalez et al [39], levels of group cohesiveness correlated positively with improvements in mental health and perceived stress. A majority of participants rated the social component of the intervention as important and reported a higher rate of social activity after the intervention.…”
Section: The Care Farms' Social Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Gonzalez et al [39], levels of group cohesiveness correlated positively with improvements in mental health and perceived stress. A majority of participants rated the social component of the intervention as important and reported a higher rate of social activity after the intervention.…”
Section: The Care Farms' Social Contextmentioning
confidence: 99%
“…The participants reported high levels of group cohesiveness, and the levels of group cohesiveness correlated positively, although not statistically significantly, with improvements in depression severity, anxiety levels, positive affect, and perceived stress levels. The participants positively evaluated the social aspects of the therapeutic horticulture intervention, and more than a third of the participants reported increased social activity after having participated in the intervention [39].…”
Section: Care Farming With Horticultural Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a developing evidence base about the effectiveness of TH and a number of studies have suggested that contact with nature is essential in helping people reestablish a sense of overall well-being (Fieldhouse 2003). It is believed that exposure to nature can have a positive effect on a person's mental well-being moreover, Gonzalez et al's (2010) prospective study of cohesiveness for people in a TH programme, found that it can be a beneficial supplementary intervention in clinical depression. Equally, it was reported by Van den Berg, (2010) and Mayer et al (2008) that exposure to nature can have a positive effect on a person's mental well-being; moreover, Gonzalez et al's (2010) Burls (2007) argued that there remains ambiguity as to the effectiveness of some models of ecotherapy, such as therapeutic horticulture.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that exposure to nature can have a positive effect on a person's mental well-being moreover, Gonzalez et al's (2010) prospective study of cohesiveness for people in a TH programme, found that it can be a beneficial supplementary intervention in clinical depression. Equally, it was reported by Van den Berg, (2010) and Mayer et al (2008) that exposure to nature can have a positive effect on a person's mental well-being; moreover, Gonzalez et al's (2010) Burls (2007) argued that there remains ambiguity as to the effectiveness of some models of ecotherapy, such as therapeutic horticulture. Moreover, Burls & Caan (2005) note that working outdoors can help individuals to connect which subsequently can alleviate social isolation, but further research is needed to understand how this occurs in relation to the types of exposure to nature (Burls 2007).…”
Section: Introductionmentioning
confidence: 99%